The geochemical composition of sediment as a proxy of provenance and weathering intensity: a case study of Southwest Nigeria’s Coastal Creeks - Phillips, Olusegun Adebayo; Falana, Adenike Omotayo; Adebayo, Adegboyega Joel (Geology, Geophysics and Environment, 2018)
The study of the geochemical composition of sediments was undertaken to evaluate the degree of weathering and appraise the relative proportion of mafic and felsic rock materials being transported from sourceto sink. Thirty-three surface sediment samples collected from the creeks were used for particle size and chemical analyses. An inductively coupled plasma-Mass Spectrometer was used to determine the elemental composition of the sediments. The clay dominated Yewa and western Badagry creeks gave evidence of higher average concentrations of Ni, Sr, Y, Nb, Sc, Co, V, and Th than the eastern end of segment of Badagry Creek. The data generated from elemental ratios such as Al2O3/TiO2, TiO2/Zr and binary plots of Th/Sc-Cr/Sc, Th-Sc, Y/Ni-Cr/V, TiO2-Zrand ICV-CIA (index of compositional variability against chemical index of alteration) showed that source sediments are composed of upper and lower crustal compositions. Also, the creeks were marked by their variation in terms of the proportion of felsic and mafic components. For instance, Yewa and western Badagry creeks are more enriched in mafic constituents, whereas the enrichment of felsic materials is significant at the eastern end of Badagry Creek. Inferring from the chemical index of alteration and plagioclase index of alteration (PIA), the Yewa and western Badagry creeks have been moderately to intensely weathered and incipient weathering was identified in the eastern end of Badagry Creek.